Advancement Of A Brand Equity-Based Social Media Marketing Activities (Smma) Model To Enhance Purchase Intention In A Private Hospital In Sidoarjo - Isnaini Fajariah; Mundakir; Sukadiono; Pipit Festi Wiliyanarti (LP2IHKI UMSurabaya, 2025)
Objective: Comprehensive researches regarding the effect of the component of brand equity on Social Media Marketing Activities (SMMA) and purchase intention are lacking. This study provides an integrated analysis of those variables on SMMA and purchase intention. Furthermore, this study expands the concept of SMMA by means of incorporating advertisement and perceived risk analyses to the concept. Methods: This study employs an explanatory research design. The research utilizes a cross-sectional data approach. Data collection was conducted through a questionnaire survey using a Likert scale for measurement. The study population consists of all inpatients who meet the inclusion criteria. The sampling technique applied was purposive sampling across various inpatient room categories, including Class 1, Class 2, Class 3, VIP, Suite Room, and President Suite. Data analysis was carried out using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of SmartPLS 4 software. Results: This study found the following: SMMA had a significant effect on brand equity with r square value 0,656, p <0.05 and purchase intention with r square value 0.631, p<0.05. Brand equity neither significantly affected purchase intention with r square value 0.003, p = 0.528 nor mediated SMMA and purchase intention p=0.544. Conclusion: Respondent characteristics have a significant influence on the variables examined. Consequently, social media marketing can be considered to have a stronger impact on respondents' decision-making compared to brand equity in the context of a hospital. Brand equity is not able to serve as a mediating variable between SMMA and Purchase Intention.